Recent advances in natural products exploitation in Streptomyces via synthetic biology - Zhao, Qiyuan; Wang, Liping; Luo, Yunzi (Engineering in life sciences, 2019)
Natural products of microbial origin have proven to be the wellspring of clinically useful compounds for human therapeutics. Streptomyces species are predominant sources of bioactive compounds, most of which serve as potential drug candidates. While the exploitation of natural products has been severely reduced over the past two decades, the growing crisis of evolution and dissemination of drug resistant pathogens have again attracted great interest in this field. The emerging synthetic biology has been heralded as a new bioengineering platform to discover novel bioactive compounds and expand bioactive natural products diversity and production. Herein, we review recent advances in the natural products exploitation of Streptomyces with the applications of synthetic biology from three major aspects, including recently developed synthetic biology tools, natural products biosynthetic pathway engineering strategies as well as chassis host modifications.